Direct production of lactic acid based on simultaneous saccharification and fermentation of mixed restaurant food waste. (1st February 2017) - Pleissner, Daniel; Demichelis, Francesca; Mariano, Silvia; Fiore, Silvia; Navarro Gutiérrez, Ivette Michelle; Schneider, Roland; Venus, Joachim
Abstract: This study introduces to a one-step process for the fermentative production of L(+)-lactic acid from mixed restaurant food waste. Food waste was used as carbon and nitrogen source in simultaneous saccharification and fermentation (SSF) using Lactobacillus sp. or Streptococcus sp. strains for L(+)-lactic acid production. Waste consisted of (w/w) 33.5% starch, 14.8% proteins, 12.9% fat and 8.5% free sugars. Lactobacillus sp. strains showed a productivity of 0.27–0.53 g L −1  h −1 and a yield of 0.07–0.14 g g −1 of theoretically available sugars, while Streptococcus sp. more efficiently degraded the food waste material and produced lactic acid at a maximum rate of 2.16 g L −1  h −1 and a yield of 0.81 g g −1 . For SSF, no enzymes were added or other hydrolytic treatments were carried out. Outcomes revealed a linear relationship between lactic acid concentration and solid-to-liquid ratio when Streptococcus sp. was applied. Statistically, from a 20% (w/w) dry food waste blend 52.4 g L −1 lactic acid can be produced. Experimentally, 58 g L −1 was achieved in presence of 20% (w/w), which was the highest solid-to-liquid ratio that could be treated using the equipment applied. Irrespective if SSF was performed at laboratory or technical scale, or under non-sterile conditions, Streptococcus sp. efficiently liquefied food waste and converted the released nutrients directly into lactic acid without considerable production of other organic acids, such as acetic acid. Downstream processing including micro- and nanofiltration, electrodialysis, chromatography and distillation gave a pure 702 g L −1 L(+)-lactic acid formulation. Graphical abstract: Highlights: An isolated Streptococcus sp. strain converted food waste efficiently into lactic acid. Max. productivity was 2.16 g L −1  h −1 and yield was 0.81 g g −1 of available sugars. Increase in solid-to-liquid ratio resulted in increased lactic acid titer. A solid-to-liquid ratio of 20% (w/w) gave 58 g L −1 lactic acid. Downstream processing resulted in a 702 g L −1 optical pure L(+)-lactic acid solution.